Passive, active, and cryotherapy post-match recovery strategies induce similar immunological response in soccer players - de Andrade Bezerra, J.; de Castro, A. C. M.; Melo, S. V. A.; Martins, F. S. B.; Silva, R. P. M.; dos Santos, J. A. R. (International Journal of Sports Science, 2014)
Recovery strategies in soccer are key for restoration of the metabolically challenged body homeostasis. To better understand the mechanisms of recovery, we analyzed the hematologic and immunological responses of three different recovery strategies after competitive soccer match play. Forty-two male professional soccer players (age, 25.7 ± 4.6 years; body mass, 75.8 ± 6.4 kg; % body fat, 11.0 ± 2.2%; VO2max, 50.4 ± 3.9 mL/kg/min) were followed-up during three consecutive days. The players were divided into three equal groups (n = 14), each of which performed one of three recovery programs after completing a soccer match: passive recovery (PR), active/jogging recovery (AR), and cryotherapy (CR). Blood samples were collected before, immediately after, and 24, 48, and 72 hrs after the match. After the match, the hematologic parameters were not significantly different between groups (p > 0.05). Regardless of the recovery strategy, significant changes were observed after the match in erythrocyte count (hemoglobin and hematocrit), yet with no physiological value. All groups showed post-match leukocytosis, which was mostly a reflection of increased neutrophil and monocyte count (p < 0.05). Match-induced leukocytosis was reversed during the recovery period. The metabolic demands of a soccer game were not sufficient to elicit a hematologic response with physiological meaning. Passive, active, and cryotherapy recovery strategies similarly reversed match-induced immunological responses in soccer players.